Skill Gap Analysis of Human Resources Between Higher Education and the Workforce in Bangka Belitung Province - Natasha; Poniman; Rifki Aditia Novaldi; Hanifa Intan Desiga (Faculty of Psychology, Universitas Negeri Yogyakarta, 2025)
This research examines the ongoing skills gap between higher education and the labor market in the Bangka Belitung Islands Province, Indonesia. The study aims to uncover the root causes of the mismatch between graduates’ competencies and industry needs while analyzing psychological and institutional factors that influence employability. Employing a qualitative case study approach, data were collected through interviews, focus group discussions, and document analysis involving universities, industries, and local government agencies. Findings indicate that the skills gap is primarily driven by three factors: misaligned curricula, limited academia–industry collaboration, and low career self-efficacy among graduates. Furthermore, the lack of exposure to practical and experiential learning environments reduces students’ confidence, adaptability, and work readiness. To address these challenges, the study recommends an integrated approach that combines experiential learning, curriculum co-creation, and strong cross-sectoral collaboration supported by local policies. Theoretically, it integrates the Skills Gap Theory, Human Capital Theory, and Link and Match Theory within an educational psychology perspective to explain how structural and psychosocial factors jointly influence human capital development. Ultimately, this study provides actionable insights for enhancing higher education’s role in regional workforce competitiveness and equipping graduates to succeed in a rapidly evolving, technology-driven labor market.